Measuring Export Competitiveness of Yarn Commodities and Textile Industry of Central Java in World Market - Ikasari, Hertiana; Ngatindriatun, Ngatindriatun (JEJAK: Jurnal Ekonomi dan Kebijakan, 2016)
Yarn commodities and textile industries are the main export commodities of Central Java. Nevertheless, there are still some problems to face. The purpose of this research is to analyze the market share and competitive advantages position of the yarn commodities and the textile industries of Central Java in the world market. The Acceleration Ratio (AR) and Trade Specialization Index (TSI) are used to analyze the export competitiveness of the yarn commodities and the textile industries. The results obtained indicates that AR of the export of yarn commodities and textile industries of Central Java is greater than 1 (AR> 1). TSI of yarn commodities and textile industries in Central Java is 0.45 and has positive value. These results indicates that Central Java has a strong market share and tends to be a regional exporter of yarn and textile commodities in the world market.